MANAJEMEN KURIKULUM PENDIDIKAN MULTIKULTURAL DI MADRASAH: KAJIAN KONSEPTUAL - Yanti Yulianti; Akhmad Fahmi Riyadhi (Eduvis : Jurnal Manajemen Pendidikan Islam, 2024)
fabric bears a strategic responsibility to cultivate multicultural competencies among its students, yet the management of multicultural education curricula within madrasah contexts remains a largely undertheorized and inconsistently practiced domain. This study investigates the conceptual and implementative dimensions of multicultural education curriculum management in madrasah, pursuing three specific objectives: (1) to analyze the theoretical foundations of multicultural education and its epistemological compatibility with Islamic educational philosophy, (2) to identify the principal challenges in the managerial implementation of multicultural curricula in madrasah, and (3) to formulate an integrated model of multicultural curriculum management grounded in Islamic values of rahmatan lil'alamin, ta'aruf, and 'adl. Employing a systematic library research methodology drawing on thirty-two peer-reviewed sources published between 2020 and 2025, the study proposes the Islamic Multicultural Curriculum Management Model (IMCMM), comprising five interconnected components: multicultural needs analysis, value-integrated curriculum design, inclusive pedagogical implementation, authentic multicultural assessment, and sustainable curriculum evaluation. Implications for madrasah curriculum developers, principals, and educational policymakers are elaborated.